Application of Geochemical and Isotopic Tools to Investigate Water Recharge and Salinization in a Coastal Phreatic Aquifer Suffering Severe Natural and Anthropogenic Constraints: Case of the Mornag Aquifer, NE Tunisia - M. Ben Alaya; J.-D. Taupin; M. H. Msaddek; I. Ayari; N. Patris; N. Chaabene; B. Toumi; F. Melki (Proceedings of the International Association of Hydrological Sciences, 2024)
The determination of the origin of salinity in the superficial aquifer of Mornag (NE Tunisia), and the understanding of its hydrological and geochemical behaviours related to severe natural and anthropogenic constraints, were approached by the combined study of chemical elements and stable isotopes (2H and 18O). This study indicates that: (1) the high salinities of the superficial aquifer of Mornag are mainly explained by the dissolution/precipitation processes of evaporite minerals in the aquifer formation, (2) the present-day recharge during rainwater infiltration brings downward a high content of nitrates and other dissolved salts, (3) infiltration of untreated sewage from the main urban areas contaminates the aquifer, (4) two other sources of dissolved salts in groundwater exist, favoured by the intensive exploitation of the phreatic aquifer. The first one is due to mineralised water infiltration from Meliane Wadi where activities, mainly a cement factory, discharge their wastewater. Intrusion of marine saltwater is the second source of salinity caused by aquifer over-exploitation. This hypothesis is supported by the high chloride concentration (>122 m e.q. L−1), Br/Cl<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="30pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="9c582698eba716b4d7a88f7baae240dc"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="piahs-385-327-2024-ie00001.svg" width="30pt" height="14pt" src="piahs-385-327-2024-ie00001.png"/></svg:svg> ratios (>1.8 ‰) and the piezometric level lower than sea level. On the other hand, the artificial recharge with low mineralization waters by the Mejerda-Cap Bon Canal and the natural recharge in the valley of wadi El Hma, contribute to a dilution of groundwater. The freshwater/saltwater mixing causes geochemical interactions modifying the water chemistry: cationic exchange, precipitation phenomena. Isotopic tools (2H and 18O) show that the water of this aquifer system has been recently recharged by direct infiltration from the boundary and in the valley of wadis.